(untitled) (Journal of Dhaka Medical College, 2023)
Background: Classification based on ascitic fluid protein has been challenged on several occasions in diverse clinical situations, including cirrhotic patients on extended diuretic treatment, cardiac ascites, 1/3 individuals with malignant ascites, spontaneous bacterial peritonitis, and even normal ascitic fluid. Objective: The study’s objective was to observe the role of serum ascites albumin gradient (SAAG) in diagnosing Ascites. Methods: This cross-sectional observational study was conducted at the Department of Medicine, Sylhet M.A.G. Osmani Medical College Hospital, Bangladesh. with a total of 100 participants with ascites following the inclusion and exclusion criteria of the study. Result: The most prevalent cause of ascites was cirrhosis, observed in 56% of the participants. Among the 56 cirrhosis patients, mean ± S.D. values of AFTP, AFAlb, SAlb, and SAAG were 2.1±1.2, 0.8±0.6, 3.1±0.7, and 2.2±0.7 respective units accordingly. According to ascitic fluid albumin values, a statistically significant relation was observed between cirrhosis and tuberculosis (P<0.01) and cirrhosis vs malignancy (P<0.01) cases. According to serum ascitic albumin gradient values, a similar significant association was also found between cirrhosis vs tuberculosis (P<0.01) and cirrhosis vs malignancy (P<0.01) cases. Conclusion: SAAG is an essential laboratory tool for the correct aetiological diagnosis of ascites. J Dhaka Med Coll. 2022; 31(1) : 120-124